Impact of Visibility and Accessibility on Healthcare Workers' Hand-Hygiene Behavior: A Comparative Case Study of Two Nursing Units in an Academic Medical Center. (April 2021) - Cai, Hui; Tyne, Intisar Ameen; Spreckelmeyer, Kent; Williams, Jennifer
Objectives: This study aims to explore the impacts of visibility and accessibility of alcohol gel-based hand sanitizer dispensers (HSDs) on healthcare workers' hand-hygiene (HH) behaviors. Background: Despite the importance of HH in reducing nosocomial infection, few empirical studies have quantitatively investigated the impacts of unit shape and size, and the resulted visibility and accessibility on HH, due to the lack of consistent methods to measure and evaluate visibility. Methods: The research was developed as a cross-sectional comparative study of two nursing units (Units A and B) with similar patient acuity and nursing care model but different shape and layout. The study applied quantitative research methods including visibility and accessibility analysis using space syntax, 1-week on-site observation, and secondary data analysis on HH compliance rates. Results: Results indicate that the unit with higher visibility and accessibility is associated with higher HH frequencies. Unit B has significantly higher visibility of HSDs, p < .001, t (60) = 4.615, and significantly higher frequency of HH activity occurrences, 5.17% versus 1.52%; p < .001, t (16.750) = 5.332, than Unit A, even though Unit B has lower HSD to bed ratio (0.708:1 vs. 1.375:1). The linear regression models also demonstrate that visibility and accessibility of HSDs are significant predictors of HH behavior. Conclusions: Overall, this exploratory study identified the importance of visibility of HSDs to improve the chances of HH. It also points out the impacts of nursing unit typology on the visibility of HSDs and in turn affects HH behavior.